(3eQjM GdYGfi aj GdYed HGdRjL GdNGbGfis - (3YHO GddWja Hf EHQGgje Hf jMji Hf GdcjGd GdCehj GdTGaYj, GHf GdcjGd,J (B950 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf eG de jYde hSgd dg Edjg WQjbG aGSJbGe hbhe CMeO MeOG jdjb HLdGdg Ydi eG CfYe s
(3BNQgG (B:s
(3LOhd GNJdGa GdeZGQH s
(3HGdfSNI LOGhd adcjIs
(3HChd GdfSNI agQSJ HCHhGH GdcJGHs
(3Ydi dhMI GdYfhGf JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B213s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs